Feasibility of eliciting the H reflex in the masseter muscle in patients under general anesthesia. Issue 1 (January 2017) - Ulkatan, Sedat; Jaramillo, Ana Maria; Téllez, Maria J.; Goodman, Robert R.; Deletis, Vedran
Highlights: We provide evidence for the feasibility of eliciting the masseter H reflex under general anesthesia. The H masseter reflex represents a new method for monitoring midbrain functional integrity. Brainstem reflexes are simple methods for monitoring brainstem and cranial nerve integrity. Abstract: Objective: To explore the feasibility of eliciting the brainstem H reflex in the masseter muscle in patients under general anesthesia. Methods: We electrically stimulated the masseteric nerve, a branch of the trigeminal nerve, and recorded ipsilateral masseteric and temporalis muscle responses. We tested eight patients who presented with trigeminal neuralgia; one patient had a temporal bone tumor and one patient had a brainstem arteriovenous malformation. All responses were elicited when patients were under general anesthesia and before the initiation of surgery. Results: The H reflex in the masseter muscle was reliably elicited in 70% of the patients. The reflexes met the usual criteria for the H reflex because they were elicited below the threshold of the direct M response, and their amplitudes decreased when the M response increased with stronger stimuli. The mean onset latencies of the masseter H reflex and the M response were 5.4 ± 1.3 ms and 2.6 ± 0.6 ms, respectively. Conclusions: In the present study, we provide evidence of the feasibility of eliciting the H reflex in the masseter muscles of patients under general anesthesia. Significance: The H reflex of the masseter muscle may represent a new method available for intraoperative monitoring. Specifically, this method may be important for the monitoring of brainstem functional integrity, particularly in the midbrain and mid-pons, in addition to the trigeminal nerve path.